A new topology for current limiting HVDC circuit breaker. (January 2019) - Li, Shuai; Zhang, Jiyuan; Xu, Jianzhong; Zhao, Chengyong
Highlights: According to the challenges of DC grid, a variable reactance DCCB is proposed. The capacitor bank is introduced to reduce the voltage stress and cost of BCB. Longer fault detection time is permitted under current limiting operation. Abstract: With the high voltage direct current Transmission (HVDC) booming, HVDC grid has received wide attention. As an essential component in HVDC grid, high voltage direct current circuit breakers (DCCB) requires urgent and intensive study. A novel topology for current limiting DCCB (CL-DCCB) is proposed in this paper. The topology consists of several units which are divided into two classes: main circuit breaker (MCB) and branch circuit breakers (BCBs). The number of inductor branches can be flexibly selected to enhance the current limiting effect. The CL-DCCB can start current limiting operation when a suspected fault occurs. When the detection circuit reveals what has happened, it can be determined whether to implement breaking operation or recover to normal state. This mode allows longer fault detection time and circuit breaker operation delay while guaranteeing the fault current within the maximum limit of the system. Finally, Simulation model and experiment prototype are built to study the design criteria for CL-DCCB. It is observed that the maximum detection delay can be extended to 12 ms. Moreover, the current limiting effect can be enhanced when the number of inductor branches or the inductance of each branch is increased.